Epidemiology and Pathogenesis of Aspiration Pneumonia - Almirall, Jordi; Boixeda, Ramon; de la Torre, Mari C.; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2024)
Aspiration pneumonia (AP) remains a critical health issue, especially among older and hospitalized patients. This review focuses on understanding the epidemiology and pathogenesis of AP, exploring key risk factors, and proposing diagnostic strategies. Aspiration pneumonia is commonly associated with hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP), where pathogens introduced into the lungs from gastric aspiration cause infection. Several factors, such as oropharyngeal dysphagia, silent aspiration, and poor oral health, contribute to increased risk, especially in frail elderly populations with chronic comorbidities. Diagnostic criteria for AP are not well-defined, complicating accurate diagnosis. Radiographic evidence of pulmonary infiltrates, history of aspiration, and clinical symptoms, such as cough and fever, guide diagnosis, but the absence of specific biomarkers remains a challenge. Furthermore, the microbiome of the lung, which shares characteristics with the oropharyngeal flora, plays a pivotal role in the development of infection. The incidence of AP is likely to increase given the growing elderly population with factors predisposing them to aspiration. It is one of the most common types of pneumonia in older adults, with its prevalence estimated to range from 5% to 24% in cases of CAP admissions. This revision highlights the growing need for comprehensive diagnostic tools and treatment protocols for AP, especially in high-risk populations such as the elderly and those in long-term care. Understanding the underlying mechanisms and the role of silent aspiration can improve prevention strategies and reduce morbidity and mortality in these vulnerable groups.
Keywords: pneumonia; aspiration pneumonia; CAP; HAP